The fate and transport of pesticide seed treatments and its impact on soil microbials - Kaiye Li; Qing Cheng; Chao Zeng; Hong Shen; Chensheng Lu (Ecotoxicology and Environmental Safety)
In order to better understand the environmental impact of systemic pesticides used in the seed treatment, we conducted a field trial by planting maize seeds treated with thiamethoxam (TMX) and the combination with difenoconazole (DFZ), two of the commonly used systemic pesticides in the seed treatment program. We found most of pesticide residues were retained in the 0–10 cm layer from soil surface. Pesticide residue levels exhibited a significant decreasing trend from the seedling to milk period. The highest level of TMX in the profile soil were 0.068 and 0.036 μg·g−1 during the elongation and seedling stages, respectively, while DFZ was always below the limit of detection. The soil bacterial abundance and community structure at the early growth stages of maize were affected by the seed treatment, but not the diversity. As TMX levels in soil diminished toward the end of maize growth period, same as the effects on soil microbials. Neither the fresh weight nor the total yield of maize was significantly different among different treatments, suggesting the planting of maize seeds treated with TMX has no apparent economic incentives to corn growers.